Enhancing immunotherapy efficacy with synergistic low-dose radiation in metastatic melanoma: current insights and prospects - Zahid Rafiq; Mingyo Kang; Hampartsoum B. Barsoumian; Gohar S. Manzar; Yun Hu; Carola Leuschner; Ailing Huang; Fatemeh Masrorpour; Weiqin Lu; Nahum Puebla-Osorio; James W. Welsh (Journal of Experimental & Clinical Cancer Research)
Abstract Recent advances in oncology research have highlighted the promising synergy between low-dose radiation therapy (LDRT) and immunotherapies, with growing evidence highlighting the unique benefits of the combination. LDRT has emerged as a potent tool for stimulating the immune system, triggering systemic antitumor effects by remodeling the tumor microenvironment. Notably, LDRT demonstrates remarkable efficacy even in challenging metastatic sites such as the liver (uveal) and brain (cutaneous), particularly in advanced melanoma stages. The increasing interest in utilizing LDRT for secondary metastatic sites of uveal, mucosal, or cutaneous melanomas underscores its potential efficacy in combination with various immunotherapies. This comprehensive review traverses the journey from laboratory research to clinical applications, elucidating LDRT’s immunomodulatory role on the tumor immune microenvironment (TIME) and systemic immune responses. We meticulously examine the preclinical evidence and ongoing clinical trials, throwing light on the promising prospects of LDRT as a complementary therapy in melanoma treatment. Furthermore, we explore the challenges associated with LDRT’s integration into combination therapies, addressing crucial factors such as optimal dosage, fractionation, treatment frequency, and synergy with other pharmacological agents. Considering its low toxicity profile, LDRT presents a compelling case for application across multiple lesions, augmenting the antitumor immune response in poly-metastatic disease scenarios. The convergence of LDRT with other disciplines holds immense potential for developing novel radiotherapy-combined modalities, paving the way for more effective and personalized treatment strategies in melanoma and beyond. Moreover, the dose-related toxicities of immunotherapies may be reduced by synergistic amplification of antitumor efficacy with LDRT.